A fluorescent sensor based on dansyl-diethylenetriamine-thiourea conjugate: a through theoretical investigation - Hien, Nguyen Khoa; Ai Nhung, Nguyen Thi; Dai, Ho Quoc; Trung, Nguyen Tien; Quang, Duong Tuan (Vietnam Journal of Chemistry, 2016)
A new dansyl-diethylenetriamine-thiourea conjugate (DT) for detection of Hg2+ ions in aqueous solution has been theoretically designed and compared to our previously published results. The synthetic path, the optimized geometric structure and the characteristics of the DT were found by the theoretical calculations at the B3LYP/LanL2DZ level. Accordingly, the DT can react with Hg2+ ion to form a product with quenched fluorescence. It is remarkable that the experimental results are in an excellent agreement with the theoretically evaluated data. Keywords. Fluorescence, chemodosimeter, dansyl, diethylenetriamine, thiourea, Mercury, TD-DFT, PET.